Gone, but not Forgotten: An Assessment Framework for Collection Reviews - Calvert, Kristin (2021)
Assessing the effectiveness of previous cancellation decisions is often overlooked in favor of current competing priorities. The authors outline their approach for evaluating journal, journal package, and database cancellations; how they evaluated whether the library could adequately support the needs of academic programs after substantial cancellations; and how to ensure the evaluative criteria used for collection review are useful and meaningful. They also provide a framework for assessing database cancellations and the criteria used in their collection reviews.